MicroRNA-17/20a impedes migration and invasion via TGF-β/ITGB6 pathway in esophageal squamous cell carcinoma - Jing, Chao (Am J Cancer Res, 2016)
Patients with esophageal squamous cell carcinoma (ESCC) have an overall poor prognosis due to invasion and metastasis. Although it has been studied extensively, the metastatic mechanisms of ESCC remains largely unclear. Here, we evaluated microRNA expression in ESCC cell sublines with distinct motility and found that microRNA-17 and microRNA-20a (miR-17/20a) dramatically impeded cell migration and invasion of ESCC in vitro and decreased pulmonary arrest in vivo. Furthermore, we identified that TGF-β receptor 2 (TGFBR2) and Smad anchor for receptor activation (SARA) served as genuine miR-17/20a targets, which are both implicated in TGF-β pathway. TGF-β treatment promoted the motility of ESCC cells, and miR-17/20a could attenuate the activation of TGF-β pathway by weakening the phosphorylation of Smad2/3 to reduce the expression of ITGB6, which was crucial in migration and invasion of ESCC cells. Moreover, evaluation of ESCC specimens revealed a close correlation between miR-17/20a, TGFBR2, SARA and lymph node metastasis. Together, our findings demonstrate that miR-17/20a suppresses cell migration and invasion of ESCC by modulating TGF-β/ITGB6 pathway, suggesting a promising strategy for diagnosis and therapy of ESCC invasion and metastasis.